Towards a Model of Cloud Computing Services for SMEs - Prasad, Acklesh; Green, Peter; Heales, Jon; Finau, Glen (ACIS, 2014)
Cloud computing can provide significant competitive advantages to the Small Medium Enterprises (SMEs) by reducing costs through a more scalable IT infrastructure model. However, the adoption of cloud based services can also entail costs and risks. The SMEs need to determine a path to adopting cloud computing services that would ensure their sustainable presence in the cloud computing environment. Extant literature on cloud computing and SMEs is a relatively new but burgeoning research area. Most papers in this field are normative in nature and lack empirical validation. Through a mixed-methods design, we develop and test a model of cloud computing adoption by the SMEs. This model will assist SMEs adopting a cloud-based strategy for sustainable improved business performance.